Interaction Effect of Cover Crop Residues and Hand Weeding of Weeds on Iceberg Lettuce (Lactuca sativa var. Iceberg) Yield - Fatemeh Ahmadnia; Ali Ebadi; Mohammad Gudarzi (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
High quality standards in vegetables is one of the most important expectation of consumers presence of weeds would also reduce the quantity and quality of crops produced. Use of cover crops could be an environmentally friendly alternative to conventional chemical and mechanical methods. To this end for controlling weeds, a factorial experiment based on a randomized complete block was conducted at the Research Farm of Mohaghegh Ardabili University with three replications in 2017. Experimental treatments were the first factor, consisting of mono culture and intercropping of rye (Secale cereal L.), hairy vetch (Vicia villosa Roth.) and control treatment (no cover crop) and the second factor consisting of one time hand weeding and two times weeding, with 15 days intervals, and without hand weeding, as control. The results showed that the highest dry biomass of cover crops obtained from rye mono culture (530.59 g.m-2) and the lowest biomass (47.85 g.m-2) from hairy vetch mono culture. The highest reduction of total weed biomass (83.24%) obtained from rye with hairy vetch without hand weeding. The highest yield of iceberg lettuce was obtained from hairy vetch mono culture with one-time hand weeding or from without hand weeding treatment (5025 and 4965 g.m-2, respectively). Also, the highest plant height, number of leaves and diameter of lettuce stem was not statistically significant difference from mono culture and intercropping of cover crops. The results showed that the combination of hand weeding and cover crop residues were more effective in controlling and reducing weed biomass, but the presence of cover crop residues in the shortron also increased the yield of iceberg lettuce through weed control.